Cyberspace : Ruang Publik Baru bagi Aktivitas Politik Muhammadiyah - Ahmad Sholikin (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
The presence of various political movements lately indicates a new appearance in the Indonesian middle class. Muhammadiyah in various previous studies has always been associated with the sociological class of the Indonesian middle class. Analysis of the middle class is always placed as